ETR 300 : The Egg House / Akmal Fadzly Hanafi ... [et al.] - Hanafi, Akmal Fadzly; Md. Emran, Zetty Akhtar; Ab Mijib, Muhamad Helmi; Hamzah, Norfaizah; Ahamad, Noor Azmy Shuhada (2000)
THE EGG HOUSE are established on all share partner agreement, they were Akmal Fadzly Hanafi, Muhamad Helrni Ab Mijib, Zetty Akhtar Emran, Norfaiz.ah Hamzah and Noor Azmy Shuhada Ahamad. This company is expected to start to run in January 01, 2005. THE EGG HOUSE is a new restaurant concept that based on eggs.